The analysis of solar energy investment, digital economy, and carbon emissions in China - Wang, Xue; Zhang, Xiaolei; Song, Jianqi (Frontiers in Energy Research, 2023)
Solar energy supports sustainable economic growth by meeting the world’s growing demand for energy while addressing climate change and reducing emissions. The literature focuses on the impact of solar energy on carbon emissions, but ignores the role of solar energy investment and the digital economy. This study investigates the influence of solar energy investment and digital economy on carbon emissions in China with the STIRPAT model. It uses the SYS-GMM method to empirically test the proposed hypotheses using provincial data for China from 2011 to 2019. The empirical results show that solar energy investment notably reduces carbon emissions. The moderating effect analysis shows that China’s digital economy has a reverse moderating effect in the process of solar energy investment, affecting carbon emissions. The results of this research can be a useful contribution to the goal of carbon emission reduction in China, and relevant policy recommendations are proposed for the findings of this research. To reduce carbon emissions and help China reduce carbon emissions targets as soon as possible, more attention should be paid to solar energy investment. The rational use of the digital economy in investing in solar energy should be on the agenda.